2022
DOI: 10.1215/03616878-10171076
|View full text |Cite
|
Sign up to set email alerts
|

Political Partisanship, Trust, and Attitudes toward COVID-19 Vaccines in Indonesia

Abstract: Context: This study aims to examine the extent to which political partisanship— measured as support for the incumbent candidate for Indonesia’s president, Joko Widodo (popularly known as Jokowi) or its former challenger, Prabowo— affects the risk perception of COVID-19 and COVID-19 vaccine hesitancy and refusal as well as beliefs about the safety and efficacy of the COVID-19 vaccine. Methods: Multinomial logistic and OLS regression analyses on a nationally representative sample of the National S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Respondents supporting an extreme right-wing party or those not participating in the election were significantly less likely to adhere to preventive measures than a supporter of the ruling conservative party [ 45 ]. A significant association between political partisanship and attitudes toward COVID-19 vaccination was also reported by other authors [ 46 50 ], and some have indicated that the effect of political views on attitudes toward COVID-19 vaccination could be mediated by a predilection to vaccine conspiracy theories [ 51 ].…”
Section: Introductionsupporting
confidence: 73%
“…Respondents supporting an extreme right-wing party or those not participating in the election were significantly less likely to adhere to preventive measures than a supporter of the ruling conservative party [ 45 ]. A significant association between political partisanship and attitudes toward COVID-19 vaccination was also reported by other authors [ 46 50 ], and some have indicated that the effect of political views on attitudes toward COVID-19 vaccination could be mediated by a predilection to vaccine conspiracy theories [ 51 ].…”
Section: Introductionsupporting
confidence: 73%
“…The political division of society as a result of the polarization that occurred in the 2017 DKI Jakarta elections and continued in the 2019 election is still visible in the form of public response to government policies related to the handling of Covid-19. Some people who do not want to be vaccinated and neglect to wear masks are those who in the 2019 election chose Prabowo-Sandi as the presidential candidate against Joko Widodo-Ma'ruf Amin (Halimatusa'diyah & Durriyah, 2022). There are fewer Prabowo supporters who are mostly from the younger generation and millennials who are willing to be vaccinated compared to Jokowi's supporters, who are mostly middle to upper class and willing to be vaccinated.…”
Section: Relation Between Religion and Identity Politicsmentioning
confidence: 99%